Volume horário de projeto para as rodovias estaduais do Ceará : análise e contribuição - Gomes, Marcos José Timbó Lima (2004)
High costs associate d with roadway construction have justified the necessity of conducting high-quality studies of transportation planning, operation, and control. Among the most important factors involved in roadway studies is the Design Hourly Volume (DHV). This parameter is usually obtained from curves hourly and although it is based on not much consistent assumptions, it has been used for dimensioning new roadways as well as for improving existing facilities. This research presents an alternative methodology to the traditional 30th - hour volume method used to obtain the DHV in State Roadways of Ceará by using data collected from 12 permanent traffic count stations. The proposed methodology emphasizes the necessity of considering economic factors oriented to the users. In this case, the decision criterion used is the percent of vehicles that, during the roadway life, will not face congestion and will encounter a level of service (LOS) better or equal to the LOS specified in the project. Therefore, the decision of constructing or improving a roadway will be justified when the costs related to the vehicles facing congestion are higher than the acceptable by the decision makers. Although the conducted analysis has limitations, this work is believed to contribute to the development of a new methodology to determine DHV that might substitute traditional concepts and methods, as well as support future research on traffic volume variation in State roadways in Ceará.